Contextualização do ensino e dialogicidade na educação física escolar: fazeres docentes em ação no ensino médio - Martins, Raphaell Moreira (2015)
The curricular component Physical Education carries historical and deep scars, pedagogical trends that were based on medical, physiological, biomechanical, behavioral, esportivista and positivist. This position produced a methodical design and technicalities class, contaminated by a distance between the teacher and the student. This work appropriates the dialog and the contextualization to expand educational opportunities to reflect the expertise of Physical Education. The objective of this research was to analyze how it shows the dialog and the contextualization of teaching in the curriculum component Physical Education in High School in the State of Ceará schools in the municipality of Caucaia, with new understandings and procedures for the Education of pedagogical practice School Physics. The methodological approach used for the development of this research and for better definition of the research instruments, was the qualitative approach. The characteristic of the research was descriptive and exploratory. The study setting was the Municipality of Caucaia - CE. The initial option was to perform a questionnaire. Sixteen teachers responded to the initial questionnaire. Being thirteen male and three female. The secondary proposal based on preliminary research findings was diving into the field of intervention, with a period of observation and interviews with the collaboration of four teachers. So we collected results through questionnaires, observations and entrevitas indicates some important considerations, in at least one class each teacher left to contextualize it. We observed a teacher who developed an entire class anchored in context. There are schools that have been concerned about the daily lives of communities of students. Contextual principles help to better understand the benefits of contextualization is well applied and developed. About dialogicity teachers already promote dialogue. When deepens the comments some principles of dialog already emerging in the pedagogical relationship. The loveliness that is a strong feeling in dialogicity was observed in the action of all the observed teachers. These results shows that the change is already occurring in physical education classes. The observations and interviews indicated that teachers are willing to improve.